The Effect of Slow Stroke Back Massage with Sunflower Oil on The Risk of Decubitus in Stroke Patients - Aisyiyah Uswatun; Mardiyono Mardiyono (Eduvest - Journal of Universal Studies, 2025)
Stroke is a neurological disorder characterized by total or partial body paralysis, commonly classified into hemorrhagic and non-hemorrhagic types. Among the 90% of acute stroke patients who experience neurological deficits, hemiparesis is one of the most frequent complications. This condition leads to prolonged immobility, increasing the risk of developing decubitus ulcers due to ischemia and hypoxia in subcutaneous tissues. Preventative measures are essential, especially in the form of early skin care interventions to maintain tissue integrity. This study aims to evaluate the effectiveness of slow stroke back massage (SSBM) using sunflower oil in preventing the risk of decubitus in stroke patients. The research employed a quasi-experimental design with pretest-posttest control groups. The intervention consisted of back massages using sunflower oil, known for its anti-inflammatory, antimicrobial, and moisturizing properties. The findings show that patients receiving the SSBM with sunflower oil had improved skin condition and reduced signs of tissue damage compared to the control group. This indicates the effectiveness of SSBM with sunflower oil in maintaining skin health and reducing the risk of pressure injuries. The study concludes that implementing simple, non-invasive interventions such as SSBM can significantly enhance the quality of care for stroke patients. These findings have implications for nursing practice, emphasizing the importance of integrating natural and cost-effective preventive care into standard stroke rehabilitation protocols.